Bone and mineral disorders among Saudi diabetics - Akhtar, Muhammad Mahmood; Alghamdi, Abdulaziz Saad; Alshehri, Abdulrahman Mohammed; Alfaraj, Hussain Zaki; Alshamrani, Abdullah Mohammed; Althagafi, Anoud Abdulrazzag; Bahanshel, Elaf Abdulqader; Aljunaid, Muataz Abdulmoghni; AlAjlani, Mohammad Abbas; Al-Khathami, Mohammed Ali; Alqahtani, Mohammed Mana (International Journal Of Community Medicine And Public Health, 2021)
Increasing bone and mineral changes which caused by both diabetes type 1 and type 2 can raise fracture risks for a period of time during illness and low blood sugar levels. The connection between diabetes and bone fragility is further complicated by the variable effects on the skeleton by various diabetic medications. Diabetic patients are at a higher risk of bone and mineral density alterations, osteoporosis and fragility fractures. Diabetic patients are often susceptible to develop various conditions due to malnutrition, uncontrolled blood sugar and lack of proper follow up regiment. Diabetics should be tested for osteoporosis risk and given effective prevention strategies. Preventing osteoporosis would require interventions such as sufficient vitamin D and calcium intake, physical exercise and exposure to sunlight.